Fostering empathy in healthcare: impact of a simulation-based educational program on professionals’ relational skills - Lidia Borghi; Maria Adelaide Morabito; Elaine C. Meyer; Philip Scilio; Elena Vegni; Giulia Lamiani (Frontiers in Medicine, 2026)
Introduction Empathy has been recognized as a crucial quality for patient-centered care and is associated with improved therapeutic outcomes and greater satisfaction of patients and clinicians. However, empathy may decline over the course of clinical practice, highlighting the need for effective educational interventions. Methods The study examined changes in empathic attitude among healthcare professionals participating in the Italian simulation-based Program to Enhance Relational and Communication Skills (PERCS-Italy) across three hospitals in Northern Italy between 2019 and 2024. The Jefferson Scale of Empathy (JSE) was administered to participants before and after attending PERCS-Italy workshops. Results A total of 303 healthcare professionals completed the pre-post training JSE assessments. Empathic attitudes increased significantly after the workshops ( t = −4.72, p < 0.001). The observed increase in empathic attitude following participation in PERCS-Italy was similar across gender and clinical discipline. Additionally, an inverse correlation between years of professional experience and empathic attitude was observed. Discussion The study reinforces the potential value of the PERCS-Italy program in increasing healthcare professionals’ relational qualities, particularly empathy.